DISKURSUS PENDIDIKAN KARAKTER DI PEGURUAN TINGGI KEAGAMAAN ISLAM PADA ERA MILENIAL - Firman Mansir (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2018)
This study examined the importance of character education in an Islamic college, especially today or which was more popular with the term of a milenial generation. The first and foremost goal of an education is the formation of students’ character (college students). Religion theory states that the goal of human moral development is the mission of religion itself, in accordance with the purpose of the Prophet Muhammad’s sending to this earth. A character education is a conscious and planned effort to instill values so that those values are internalized in the college students and to produce a good behavior or in the religious language is often called as Muhsin. Therefore, a character education is essentially an education which seeks to instill and spread virtues or in this case a Rahmatan Lil’alamin. This research was a literature review (library research) which was sourced from the library materials using a qualitative approach. Thus, the research activity was an exploration of a number of data both primary and secondary with several concrete steps such as reading and in-depth studying the primary data such as books of the research results, theses or dissertations related to the character education and Islamic education. Character education for college students is needed because all this time students are only preoccupied with lecture materials in the classroom, but lack of attention to the meaning and value behind the process it self.